The Effect Of Workload And Adversıty Quotıent On Employee Performance At X Company Wıth Work Motıvatıon As A Medıatıng Varıable - Raihan Gunaringtyas Hatmanti; Fetty Poerwita Sary (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Employee performance is a very important aspect of the company and cannot be separated from work motivation. To get optimal performance, it is necessary to pay attention to the factors that affect performance. In company X, there is an assessment of workload and adversity quotient to determine employee performance. This study aims to identify the effect of workload and Adversity Quotient (AQ) on employee performance in company X, by considering work motivation as a mediating variable. The method that used in this research is descriptive analysis by collecting data through questionnaires distributed to employees of company X. And data processing analysis in this study used SEM-PLS. The sample in this study is using proability sampling with simple random sampling. The results of this study are workload has a significant effect on employee performance, as well as adversity quotient has a significant positive effect on employee performance, and work motivation is a good mediating variable in this study. Thereby, company X can pay attention to workload, adversity quotient in employees, and work motivation to improve performance to be more optimal and efficient.